Perubahan Harga Saham Perusahaan Tekstil dan Garmen di Indonesia - Sriyono Sriyono; Aminatus Solihah (Jurnal Ekonomi Modernisasi, 2018)
The purpose of this study was to determine the implications of net profit margins, debt to equity ratio and quick ratio to stock prices. The population used is various textile and garment subsector industries in the Indonesia Stock Exchange in 2011-2015. The sampling technique used is purposive sampling. The results showed that the net profit margin had a significant and positive influence on stock prices while capital structure and quick ratio had no significant effect on stock prices. Managerial implications of research that textile and garment companies prioritize corporate profitability to increase stock prices.